Spray volume optimization with UAV-based herbicide application for effective droplet deposition and weed control in direct-seeded rice - Paul, Ratchagar Arockia Infant; Palanisamy, Murali Arthanari; Peramaiyan, Panneerselvam; Kumar, Virender; Bagavathiannan, Muthukumar; Gurjar, Bholuram; Vijayakumar, Shanmugam; Djanaguiraman, Maduraimuthu; Pazhanivelan, Sellaperumal; Ramasamy, Kavitha (Frontiers in Agronomy, 2024)
Unmanned aerial vehicles (UAVs) represent a cutting-edge technology that holds the promise of revolutionizing the conventional tasks carried out in the realm of agriculture. On a global scale, UAVs are gaining prominence for pesticide applications, particularly with a focus on utilizing low spray volumes. Nevertheless, there remains a notable gap in research concerning the impacts of employing low spray volumes on herbicide efficacy. Hence, multi-location field studies were conducted at Agricultural Research Station, Bhavanisagar and Wetland Station, Coimbatore, Tamil Nadu, India in 2022 to evaluate the impact of different spray volumes using UAV and Knapsack Manual Sprayer (KMS) on droplet deposition, droplet density, and weed control efficacy. The treatments included UAV sprays at 30 and 45 L ha-1, as well as KMS at 500 L ha-1, with a weedy check as a control. Bispyribac-sodium 10% SC was applied at a rate of 35 g a.i ha-1 during the 2-to 3-leaf stage of the crops. The results revealed that droplet deposition, area coverage, and volume median diameter were affected by sprayer type (UAV and KMS). However, the two spray volumes tested using the UAV method provided similar droplet parameters. The KMS system at 500 L ha-1 exhibited the highest droplet deposition, while the UAV system achieved better droplet distribution at a spray volume of 30 L ha-1. Remarkably, the UAV system at 30 L ha-1 demonstrated effective weed control, which was statistically comparable to the KMS system at 500 L ha-1. These findings emphasize that the UAV spraying system with a spray volume of 30 L ha-1, delivering effective weed control while utilizing less carrier volume compared to the manual knapsack spraying method. Thus, the UAV spray system has great potential as a viable alternative to manual knapsack spraying for herbicide application in direct-seeded rice.